The impact of the COVID-19 pandemic on swimmers in Poland - Ogonowska-Slodownik Anna; Kawa Kamil; Morgulec-Adamowicz Natalia (Sciendo, 2022)
Study aim: To assess the impact of the COVID-19 pandemic on health, lifestyle, training loads and competition starts of swimmers in Poland in 2020.